Using High-Density Polyethylene and Novolac Polymers to Improve the Properties of Gypseous Soil - Khazaal, Maher M.; Mohammed Shafiqu, Qassun S. (Al-Nahrain Journal for Engineering Sciences, 2024)
This study explores the impact of adding high-density polyethylene (HDPE) and Novolac polymers to gypseous soil from Tikrit City, Iraq, to enhance its geotechnical properties. The soil contained 38% gypsum, and the polymers were added in varying proportions (1%, 3%, 6%). Both polymers improved maximum dry density, optimum moisture content, and reduced collapse potential (Ic). The collapse potential was reduced by 64%, 77.7%, and 83.2% at 1%, 3%, and 6% HDPE content, respectively. The collapse potential was reduced by 82.3%, 74.8%, and 51.9% at 1%, 3%, and 6% Novolac polymer content, respectively. In the dry conditions, the internal friction angle increased by about 22.9% and 5.7% as the HDPE content was increased by 3% and 6% respectively. Adding Novolac polymer also increased the internal friction angle by about 5.7% by the addition of 3% Novolac polymer. In soaked conditions, the best increase in internal friction angle (?) was 30% with the addition of 3% HDPE polymer. the internal friction angle increased by about 26.7% by adding 1% and 3% of Novolac polymer. The study concludes that adding HDPE and Novolac polymers can improve geotechnical properties, but their effect on CBR is complex and depends on the polymer percentage added and soil moisture state.